2022
DOI: 10.1093/toxres/tfac009
|View full text |Cite
|
Sign up to set email alerts
|

Cerium oxide nanoparticles attenuate the renal injury induced by cadmium chloride via improvement of the NBN and Nrf2 gene expressions in rats

Abstract: Background Cadmium (Cd) is a highly toxic heavy metal that adversely affects both human and animal health. Chronic cadmium exposure causes serious kidney damage. The current study investigated the protective role of cerium oxide nanoparticles (CeO2NPs) against cadmium chloride (CdCl2)-induced renal injury. Method One hundred and twenty male albino rats were divided into 6 equal groups. Group (C): considered as control group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…It is involved in the regulation of the expression of antioxidants, such as GST (45). In the absence of Nrf2, liver regeneration is significantly delayed and hepatocyte death is also increased (46). It has been demonstrated that Co and sevoflurane both downregulate Nrf2 (44,46).…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in the regulation of the expression of antioxidants, such as GST (45). In the absence of Nrf2, liver regeneration is significantly delayed and hepatocyte death is also increased (46). It has been demonstrated that Co and sevoflurane both downregulate Nrf2 (44,46).…”
Section: Discussionmentioning
confidence: 99%
“…CeO 2 NPs ameliorated nephrotoxicity by reversing the downregulation of the nuclear factor erythroid 2related factor 2 (Nrf2) gene, which plays a pivotal role in antioxidant response element (ARE)-dependent gene expression. 65 In AKI induced by peritonitis, 20 nm CeO 2 NPs counteract ROS, attenuate caspase-3 activation, reduce the loss of F-actin, alleviate renal tubular injury, and ultimately safeguard renal function. 62 Numerous additional metals (such as Ir, Au, Cu, Mo, Ag, Pt, and Zn) 70,75,78,81,82 and metal oxides have also been shown to exhibit catalase activity.…”
Section: Metal and Metal-basedmentioning
confidence: 99%
“…Furthermore, research indicates CeO 2 NPs suppressed the cadmium-induced upregulation of the nibrin (NBN) gene, which is involved in DNA replication and repair processes. CeO 2 NPs ameliorated nephrotoxicity by reversing the downregulation of the nuclear factor erythroid 2-related factor 2 (Nrf2) gene, which plays a pivotal role in antioxidant response element (ARE)-dependent gene expression . In AKI induced by peritonitis, 20 nm CeO 2 NPs counteract ROS, attenuate caspase-3 activation, reduce the loss of F-actin, alleviate renal tubular injury, and ultimately safeguard renal function …”
Section: Therapeutic Nanomaterials For Akimentioning
confidence: 99%
“…55 CeO 2 NPs have good biocompatibility and can prevent cadmium-induced kidney injury by clearing ROS, downregulating apoptotic genes, and upregulating antioxidation-related genes. 56…”
Section: Application Of Antioxidant Enzymes In Akimentioning
confidence: 99%